The Traces of Al-Hafiz Al-Dhahabi in the Tazheeb Tahzeeb Al-Kamal on the Tahzeeb Al-Kamal in the Names and Genealogies of the Narrators and the Distinction between Them - Okour, Hajar Khalifah; Alomari , Mohammad Ali Qasem (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The research aims to stand at two scholars of men in Al-Hadith Al-Sharif, namely Al-Hafiz Jamal Al-Din Abu Al-Hajjaj Al-Mezzi, and Al-Hafiz Shams Al-Din Muhammad bin Qaymaz Al-Dhahabi. The research dealt with the traces of the Al-Hafiz Al-Dhahabi, in his book Tadheeb AL- tahdeeb, on the book Tahdeeb AL-kamal in the Names of Men, by Al-Hafiz Al-Mezzi, with regard to names, nicknames, and titles, and highlighting them and showing their size. Methods: The study followed the inductive approach of the book “Tazheeb al-Tahzheeb” to extract the traces and classify them to find out what is related to names and surnames, and then use the analytical method, by classifying the traces, and examining them, to reach the traces that are related to names, nicknames, and titles. The study also adopted the critical approach to study these traces and indicate what is likely from them. Results: The study was based on fourteen tracks, in which Al-Dhahabi tracked the book Refinement of Perfection, which consisted of five tracks in controlling names, nicknames, and epithets, and nine tracks in the agreement and the parting. It has been shown in most traces that the right was with Al-Dhahabi. His expressions were very polite and appreciative of the book and its companion. Conclusions: The study concluded that traces and reflections are an important science that students need to pay attention to, because of their important role in shaping the scientific personality.